Amalgamation of Mathematics in Economics: A Historical and Theoretical Perspective - Devkota, Nanu Maya (Journal of Development Review, 2025)
The integration of mathematical models into economics has evolved into a cornerstone of contemporary economic research. This progression, marked by increasing algebraic usage, reflects the discipline's shift toward a structured, rigorous framework. Despite its value, the adoption of mathematical methods faced challenges and debates over their practical efficacy, highlighting the dynamic interplay between theoretical insights and practical applications to shape modern economic analysis. The paper addresses the lack of a simple and consolidated framework of essential mathematical concepts and their applications in economics. Focusing on that problem, this paper aims to examine the evolution of mathematics in classical economics. Moreover, role of mathematics in solving contemporary economic problems related to decision-making and forecasting, and its contribution to improving economic efficiency are also considered. To fulfill objectives, a qualitative method with descriptive analysis is used to examine the foundational works of classical economists and its application in current economic issues. Mathematical models and matrix algebra are used to forecast trends, maximize resources, and examine interdependencies among economic variables in Nepal, while game theory directs strategic policies in areas like hydropower trade. The findings reveals that mathematical tools and models have transformed economic analysis, offering a robust framework for addressing complex policy issues and promoting sustainable development, particularly in Nepal and beyond.